2015
DOI: 10.1111/nmo.12601
|View full text |Cite
|
Sign up to set email alerts
|

Postinfectious irritable bowel syndrome after travelers' diarrhea – a cohort study

Abstract: Our findings underline the close linkage of mental and somatic processes for the manifestation of PI-IBS. Screening for psychiatric comorbidities in patients with severe gastrointestinal infections may allow identifying groups at high risk for PI-IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
(100 reference statements)
1
7
0
1
Order By: Relevance
“…We found IBS‐affected individuals having not only higher scores for depression at the time of SHIP assessment, but also a more frequent history of a recurrent depressive episode in the past. This is in line with several other studies . This association raises the question, whether IBS is the cause or consequence of depression .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found IBS‐affected individuals having not only higher scores for depression at the time of SHIP assessment, but also a more frequent history of a recurrent depressive episode in the past. This is in line with several other studies . This association raises the question, whether IBS is the cause or consequence of depression .…”
Section: Discussionsupporting
confidence: 93%
“…They further postulated at least two subgroups within the IBS-affected cohort with a mainly mental vs a mainly physical etiology of symptoms. Also, the interaction of both, mental and physical factors, is reported in the literature, 51 whereas a high number of comorbidities are suspected to be related to a more psychological IBS etiology. 20 We found IBS-affected individuals having not only higher scores for depression at the time of SHIP assessment, but also a more frequent history of a recurrent depressive episode in the past.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we included 45 studies (n=21,421 participants with IE exposure) that reported the prevalence of PI-IBS. 4, 5, 713, 1517, 20, 23, 2959 The flow diagram summarizing study identification and selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Ähnliche Schlüs-se lassen prospektive Daten zum sog. postinfektiösen Reizdarmsyndrom (PI-RDS) zu, das durch akute Darminfektionen ausgelöst wird [24,26]. Chronische Stressbelastung und Depressivität erhö-hen dabei nachweislich das Risiko des PI-RDS.…”
Section: Affektstörungen Und Chronischer Stressunclassified